2023
DOI: 10.2147/prbm.s399824
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Teacher–Student Relationship and Adolescent Emotional Intelligence: A Chain-Mediated Mediation Model of Openness and Empathy

Abstract: Background As the role of emotional intelligence has been increasingly explored, researchers generally agree that emotional intelligence is a better predictor of individual success. And fortunately, emotional intelligence is somewhat easily shaped. Schools are important microsites for the shaping of an individual’s emotional intelligence. Good teacher-student relationship contribute to the shaping and development of students’ emotional intelligence. Objective Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…Firstly, empathy directly and positively impacts caring ability, and also plays a mediating role in the association between emotional intelligence and caring ability, hypothesis 2, hypothesis 3 and hypothesis 7 are supported, similar to previous research ( Lina et al, 2022 ; Xiang et al, 2022 ; Wan et al, 2023 ). Empathy refers to the ability to comprehend and resonate with others’ emotions as if they were one’s own.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Firstly, empathy directly and positively impacts caring ability, and also plays a mediating role in the association between emotional intelligence and caring ability, hypothesis 2, hypothesis 3 and hypothesis 7 are supported, similar to previous research ( Lina et al, 2022 ; Xiang et al, 2022 ; Wan et al, 2023 ). Empathy refers to the ability to comprehend and resonate with others’ emotions as if they were one’s own.…”
Section: Discussionsupporting
confidence: 86%
“…It is often portrayed as individuals’ ability to empathize with the other person ( Ioannidou and Konstantikaki, 2008 ). Previous research has shown that more empathic behavior tends to occur in people with higher emotional intelligence ( Silva and Toledo Júnior, 2021 ; Wan et al, 2023 ). It is clear that individuals who have strong perception, identification and control of their own emotions are equally able to gain mastery over others.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…12. A good teacher should be kind, have a big heart, and always be ready to listen. 13,14 Good lectures trigger enthusiasm, and teachers are often passionate about the subject they teach, even if it is not that exciting. 15 As an aid to learning, laughter should be applied during lectures as it helps relieve students' pressure by lightening the tone and providing a minor break from what may seem like a lengthy, monotonous session.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, participants from companies in Spain underscore the importance of team EQ in boosting the positive emotional state or passion of subordinates collectively when coupled with transformational leadership behaviors (Mindeguia et al, 2021). Wan et al (2023) further reveals the significance of EQ in cultivating the intimacy and supportive nature of teacher-student relationship, facilitated by openness and empathy in mainland China. Although promoting trust and communication, EQ measured by the Emotional Intelligence Scale does not show significance in conflict resolution among Asian university students (Der Foo et al, 2004).…”
Section: Eq Rq and Group-based Practicementioning
confidence: 98%